"Who am I to tell them how to coach?"- An analysis of coach developers' professional identity formation - Davidson, J.; Townsend, R. C. (International Sport Coaching Journal, 2024)
Coach developers play a critical role in the development of coaches. However, coach developers themselves remain under-researched, in particular the socially mediated process of becoming a coach developer is poorly understood. Eleven coach developers working across Regional and National Sports Governing Bodies took part in a series of interviews and in situ observations over the course of 12 months. Engaging a reflexive thematic analysis, this paper focuses on the power relations that contour the transitions into coach developer roles. Specifically, the analysis depicts an identity-making process in which power is exerted through different sites and modalities that structure and regulate coach developers` practice and roles through shared discourses. In efforts to secure their positions and maintain legitimate identities, coach developers operated within an uncritical selective culture, which saw them wield, maintain, and enhance the power provided to them. Building on existing research, we examine the contested nature of what it means to be a coach developer, specifically showcasing the navigation of inherently unstable professional learning cultures and critiquing coach developer training. This work begins to address calls for the voices of coach developers in their research, while identifying the reproduction of a cultural orthodoxy, and the lack of effective in situ coach developer training. Implications from the research suggest that further support and development are required in the training of coach developers in situ, as well as the need for research to interrogate the language and discourse framing the role.